A crystal form of etomomod and its preparation method and application

By studying and preparing crystal form A and B of Etomode, the problem of insufficient research on crystal form in the existing technology is solved, and its physical and chemical stability and solubility are optimized, which is more suitable. Industrialized pharmaceutical preparations.

CN116217507BActive Publication Date: 2024-12-20JIANKUAN (SUZHOU) BIOTECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211659300.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2024-12-20
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

There is a lack of research on the crystal form of Etomod in the prior art, which affects the dissolution performance and efficacy of pharmaceutical preparations. The main drug ingredient used in pharmaceutical preparations is mixed crystals, which affects the quality of the preparations.

Method used

Two crystal form A and Crystal B of Etomode are provided and their preparation methods are prepared by heating and dissolving and evaporating the solvent in methanol, and Crystal B is spray-dried by spray-drying the crystal form A in a mixed solvent. Made, its physical and chemical stability and solubility are optimized.

Benefits of technology

Crystal Form A has lower wettability, higher solubility, better mechanical stability, lower fluidity and adhesion, and is suitable for industrial production and has good prospects for pharmaceutical industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217507B_ABST
    Figure CN116217507B_ABST
Patent Text Reader

Abstract

The present invention provides a crystal form of etomomod and a preparation method and application thereof. The crystal form relates to crystal form A and crystal form B. Crystal form A and crystal form B can exist stably, have low hygroscopicity, high solubility, good mechanical stability and low fluidity, as well as low adhesion and good compressibility, and have prospects for pharmaceutical industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of medical technology, and specifically relates to a crystal form of etomomod and a preparation method and application thereof. Background Art

[0002] Atromod is an immunosuppressant targeting the S1P1 receptor and a new drug for the treatment of psoriasis. Its chemical name is 2-amino-2-{2-(4'-(2-ethyloxazol-4-yl)-[1,1'-biphenyl]-4-yl)ethyl}-1,3-propanediol hydrochloride, and its structural formula is as follows:

[0003]

[0004] Although the preparation method of etomomod is disclosed in the existing technology, the crystal form has not been studied. If the main drug component used in the preparation of the drug preparation is a mixed crystal, it may have an important impact on the dissolution performance and efficacy of the preparation product. Therefore, the study of the crystal form of etomomod is of great significance for the subsequent preparation development and drug treatment effect. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a crystalline form of etomomod and a preparation method and application thereof.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] On the one hand, the present invention provides a crystalline form A of etomomod, wherein the crystalline form A has the following diffraction peaks at 2θ diffraction angles in the X-ray diffraction pattern: 9.295°±0.2°, 14.026°±0.2°, 17.107°±0.2°, 17.774°±0.2°, 21.458°±0.2°, 21.937°±0.2°, 22.396°±0.2°, 26.883°±0.2°, 28.236°±0.2°, 28.534°±0.2°.

[0008] On the other hand, the present invention provides a method for preparing the crystalline form A of etomomod as described above, the preparation method comprising the following steps: adding an etomomod sample to methanol, heating to dissolve, and evaporating the solvent to obtain the crystalline form A.

[0009] Preferably, the temperature is increased to 50-60°C, such as 50°C, 53°C, 55°C, 58°C or 60°C.

[0010] On the other hand, the present invention provides a crystalline form B of etomomod, wherein the crystalline form B has the following diffraction peaks at 2θ diffraction angles in the X-ray diffraction pattern: 9.025°±0.2°, 15.108°±0.2°, 16.213°±0.2°, 17.352°±0.2°, 18.151°±0.2°, 19.143°±0.2°, 21.230°±0.2°, 22.113°±0.2°, 23.537°±0.2°, 24.755°±0.2°, 27.928°±0.2°.

[0011] On the other hand, the present invention provides a method for preparing the crystalline form B of etomomod as described above, the preparation method comprising the following steps:

[0012] The crystal form A of Etomod is added to a mixed solvent, dissolved until clear, and the solution is spray-dried to obtain the crystal form B of Etomod.

[0013] Preferably, the mixed solvent is a mixed solvent of acetone and water, or a mixed solvent of ethanol and water.

[0014] Preferably, the volume ratio of acetone to water is 1:0.5-2, for example 1:0.5, 1:0.6, 1:0.8, 1:1.0, 1:1.3, 1:1.5, 1:1.8 or 1:2.

[0015] Preferably, the volume ratio of ethanol to water is 1:0.1-1, such as 1:0.1, 1:0.3, 1:0.5, 1:0.8 or 1:1.

[0016] In the present invention, it is found that atomide has multiple crystal forms, including but not limited to crystal form A, crystal form B, crystal form C and crystal form D. Among them, crystal form A and crystal form B have pharmaceutical industrial application value. Through the comparison of multiple indicators such as stability, solubility, hygroscopicity, morphological research, powder properties and mechanical properties, it is found that compared with crystal form B, crystal form A has a simple preparation method, high efficiency, is suitable for industrial production, has low cost, and has lower hygroscopicity, higher solubility, and better physical and chemical stability and mechanical stability.

[0017] On the other hand, the present invention provides a pharmaceutical composition, comprising the crystalline form A of etomomod as described above and / or the crystalline form B of etomomod as described above, and a pharmaceutically acceptable excipient.

[0018] In another aspect, the present invention provides use of the above-mentioned crystalline form A of etomomod or the above-mentioned crystalline form B of etomomod in the preparation of an S1P1 receptor immunosuppressant.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The crystalline form A and crystalline form B of Etomod of the present invention can exist stably, wherein the crystalline form A has lower hygroscopicity, higher solubility, better mechanical stability and lower fluidity, as well as lower adhesion and good compressibility, and has good prospects for pharmaceutical industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the X-ray powder diffraction (XRPD) spectrum of Atromod Form A.

[0022] Figure 2 This is a differential scanning calorimetry (DSC) diagram of Atromod Form A.

[0023] Figure 3 This is the thermogravimetric (TGA) diagram of Atromod Form A.

[0024] Figure 4 This is the FT-infrared (FT-IR) spectrum of Atommod Form A.

[0025] Figure 5 This is the dynamic moisture sorption (DVS) diagram of etomomod crystal form A.

[0026] Figure 6 This is the X-ray powder diffraction (XRPD) spectrum of Atromod Form B.

[0027] Figure 7 This is the differential scanning calorimetry (DSC) diagram of Atromod Form B.

[0028] Figure 8 This is the thermogravimetric (TGA) diagram of Atromod Form B.

[0029] Fig. 9 This is the FT-infrared (FT-IR) spectrum of Atromod Form B.

[0030] Fig.10 This is the dynamic moisture sorption (DVS) diagram of etomomod crystal form B.

[0031] Fig.11 This is the X-ray powder diffraction (XRPD) spectrum of Atromod Form C.

[0032] Fig.12 The X-ray powder diffraction (XRPD) superposition spectrum of Atromod Form C before and after drying.

[0033] Fig.13 This is a thermogravimetric (TGA) graph of a sample of etomode form B placed under 92.5% RH for 30 days.

[0034] Fig.14This is the X-ray powder diffraction (XRPD) spectrum of Form D of Atommod.

[0035] Fig.15 This is the differential scanning calorimetry (DSC) diagram of Atromod Form D.

[0036] Fig.16 This is the thermogravimetric (TGA) diagram of Atromod Form D.

[0037] Fig.17 X-ray powder diffraction (XRPD) overlay for the stability of Form A of Etomod.

[0038] Fig.18 X-ray powder diffraction (XRPD) overlay for the stability of Form B of Etomod.

[0039] Fig.19 The X-ray powder diffraction (XRPD) superposition of Atromod Form A before and after grinding.

[0040] Fig. 20 The X-ray powder diffraction (XRPD) superposition of Atromod Form B before and after grinding.

[0041] Fig.21 The X-ray powder diffraction (XRPD) superposition diagram of Atromod Form A before and after compression.

[0042] Fig. 22 The figure shows the X-ray powder diffraction (XRPD) superposition of Atromod Form B before and after compression.

[0043] Fig.23 The X-ray powder diffraction (XRPD) superposition diagram of Atromod Form A before and after DVS testing.

[0044] Fig.24 This is an X-ray powder diffraction (XRPD) overlay of Etomod Form B before and after DVS testing.

[0045] Fig.25 The figure shows the microscopic observation result of etomomod crystal form A, and the scale bar is 20 μm.

[0046] Fig.26 The figure shows the microscopic observation result of etomomod crystal form B, and the scale bar is 10 μm. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] In the embodiment of the present invention, the instrument used for the X-ray powder diffraction test is the D2 Phaser of Bruker. The differential scanning calorimetry test uses the DSC 250 differential scanning calorimeter provided by TA Instruments. The thermogravimetric analysis uses the TGA 55 thermogravimetric analyzer provided by TA Instruments. The FT-infrared test uses the Thermo Fourier transform infrared spectrometer, model ID1-summit. The dynamic moisture adsorption test uses the Surface Measurement System (SMS)-DVS Intrinsic. The microscope test uses the microscope produced by Suzhou Nanguang Electronic Technology Co., Ltd., model NJF-120A.

[0049] Example 1 Preparation of Etomod Crystal Form A

[0050] Weigh 3.5 g of the atomide sample into a 500 mL glass single-mouth bottle, add 400 mL of methanol and heat to 55 ° C to dissolve the sample. After the sample is dissolved, transfer it to a rotary evaporator to evaporate the solvent to obtain 2.9 g of solid (yield 82.8%), and then perform XRPD detection on the obtained solid. According to XRPD detection, the obtained solid is atomide crystal form A.

[0051] Analysis results: Purity tested by HPLC: 98.84%.

[0052] 1H-NMR (400MHz, DMSO-d6): δ = 8.54 (s, 1H), 7.97 (s, 3H), 7.84 (d, J = 8.3Hz, 2H), 7.71 (d, J = 8.3Hz, 2H), 7.65 (d, J = 8.1Hz, 2H), 7.33 (d, J = 8. 0Hz, 2H), 5.44 (t, J = 5.3Hz, 2H), 3.57 (d, J = 4.7Hz, 4H), 2.82 (q, J = 7.6Hz, 2H), 2.72–2.64 (m, 2H), 1.91–1.82 (m, 2H), 1.30 (t, J = 7.6Hz, 3H).

[0053] Figure 1 The XRPD spectrum of the isolated 2-amino-2-{2-(4′-(2-ethyloxazol-4-yl)-[1,1′-biphenyl]-4-yl)ethyl}-1,3-propanediol hydrochloride Form A is shown, and the XRPD parameters in the figure are summarized in Table 1 below.

[0054] Table 1 XRPD parameters of Form A

[0055]

[0056]

[0057] The crystalline form A has Figure 2 As shown in the differential scanning calorimetry (DSC) diagram, it can be seen that when Form A is heated to 225°C (starting temperature), an endothermic peak appears, which is the melting endothermic peak of Form A.

[0058] The crystalline form A has Figure 3 Thermogravimetric (TGA) graph shown in the figure shows that when Form A is heated to 150°C, it has a mass loss of about -0.2% (the instrument error is ±0.2%).

[0059] The crystalline form A has Figure 4 As shown in the Fourier transform infrared (FT-IR) diagram, it can be seen that by characterizing Form A using Fourier transform attenuated total reflection infrared spectroscopy (FT-IR), qualitative infrared spectroscopy data can be obtained, which can prove that the product conforms to the structure of etomomod.

[0060] The crystalline form A has Figure 5 As shown in the dynamic moisture sorption (DVS) diagram, it can be seen from the figure that the DVS spectrum of Form A shows that the sample has a moisture gain of 0.14% and has no or almost no hygroscopicity (moisture adsorption at 25°C / 90%RH).

[0061] Example 2 Preparation of Etomod Crystal Form B

[0062] Weigh 5 g of the Atromod Form A sample into a 500 mL glass single-mouth bottle, add 225 mL of acetone and 225 mL of water to dissolve the sample. After the sample is dissolved, spray dry it to obtain 2.67 g of solid (yield: 53.4%). XRPD detection shows that the obtained solid is Atromod Form B.

[0063] Analysis results: Purity determined by HPLC: 98.85%

[0064] 1 H-NMR (400MHz, DMSO-d6): δ = 8.53 (s, 1H), 8.08–7.79 (m, 5H), 7.71 (d, J = 8.3Hz, 2H), 7.65 (d, J = 7.9Hz, 2H), 7.32 (d, J = 7.9Hz, 2H), 5.42(t,J=5.0Hz,2H),3.56(d,J=4.8Hz,4H),2.83(q,J=7.6Hz,2H),2.71–2.63(m,2H),1.91–1.79(m,2H),1.30(t,J=7.6Hz,3H).

[0065] Figure 6The XRPD spectrum of isolated 2-amino-2-{2-(4′-(2-ethyloxazol-4-yl)-[1,1′-biphenyl]-4-yl)ethyl}-1,3-propanediol hydrochloride Form B is shown, wherein the XRPD parameters are summarized in Table 2.

[0066] Table 2 XRPD parameters of Form B

[0067]

[0068]

[0069] The crystal form B has Figure 7 The differential scanning calorimetry (DSC) diagram shown in FIG. 1 shows that the first endothermic peak appears when the crystalline form B is heated to 142° C. (starting temperature); the second endothermic peak appears when the crystalline form B is heated to 233° C. (starting temperature).

[0070] The crystal form B has Figure 8 Thermogravimetric (TGA) graphs shown show that when Form B is heated to 150° C., it has a mass loss of about -0.1% (the instrument error is ±0.2%). The TGA results show that Form B is an anhydrous substance.

[0071] By characterizing Form B using Fourier transform attenuated total reflection infrared spectroscopy (FT-IR), infrared spectroscopy qualitative data can be obtained. The FT-IR spectrum of Form B is as follows: Fig. 9 shown.

[0072] The crystal form B has Fig.10 The dynamic moisture sorption (DVS) diagram shown in the figure shows that the sample has a moisture absorption weight increase of 4.6%, and is hygroscopic (moisture absorption at 25°C / 90%RH).

[0073] Example 3 Preparation of Etomod Crystal Form B

[0074] Weigh 5 g of the Atromod Form A sample into a 500 mL glass single-mouth bottle, add 270 mL of ethanol and 30 mL of water to dissolve the sample. After the sample is dissolved, cool it down to precipitate crystals, and obtain 3.1 g of solid (yield: 62%). XRPD detection shows that the obtained solid is Atromod Form B.

[0075] Example 4 Preparation of Etomod Crystal Form C

[0076] Weigh 250 mg of atomidine crystal form B sample into a 10 mL glass vial, add 5 mL of pH = 1.0 hydrochloric acid aqueous solution to form a suspension, and stir at room temperature for 20 hours. The results of XRPD detection are as follows Fig.11 As shown, the obtained solid is atommod crystal form C.

[0077] The above sample was placed at 50°C under vacuum and dried overnight, and then subjected to XRPD analysis. Fig.12 As shown, the solid part is transformed into atomide form A; the above sample is purged with nitrogen at room temperature for 3 hours, and XRPD is performed on it. Fig.12 As shown in FIG. 1 , the solid part is transformed into aitmod crystal form A. The sample of aitmod crystal form B after DVS test is transformed into aitmod crystal form C, and its XRPD comparison diagram is shown in FIG. Fig.24 Atomodus Form B was placed under 92.5% RH for 30 days and then transformed into Atomodus Form C. Its XRPD comparison chart is shown in Fig.18 The sample was tested by TGA, and its TGA results were shown in Fig.13 From the above results, it is inferred that Form C is an unstable tubular hydrate, which is prone to crystal transformation during drying and storage, and it is difficult to prepare a pure phase.

[0078] Analysis results of the dried samples:

[0079] Purity: 98.81%.

[0080] 1 H-NMR (400MHz, DMSO-d6): δ = 8.53 (s, 1H), 7.94 (s, 3H), 7.86-7.82 (m, 2H), 7.74-7.70 (m, 2H), 7.67-7.63 (m, 2H), 7.35-7.31 (m, 2H) ,5.43(t,J=5.2Hz,2H),3.56(d,J=5.1Hz,4H),2.83(q,J=7.6Hz,2H),2.71-2.64(m,2H),1.89-1.82(m,2H),1.30(t,J=7.6Hz,3H).

[0081] Example 5 Preparation of Etomod Crystal Form D

[0082] 13 mg of the crystalline form B sample of Atromod was weighed and placed in an aluminum pan. The instrument model was TA Instruments TGA 25. The temperature was raised to 180°C at a heating rate of 10°C / min. The temperature was kept constant for 40 minutes under nitrogen purge and then cooled to room temperature to obtain an off-white solid. The results of XRPD detection are as follows: Fig.14 As shown, the obtained solid is atommod crystal form D.

[0083] Atommod crystal form D was obtained by heating experiment and is difficult to enlarge. Its TGA graph is shown in Fig.16The sample weight loss before 150°C was 1.4%. The heated sample was subjected to ion chromatography, and the chloride ion content was 8.32% (theoretical chloride ion content was 8.83%), and the HPLC purity test result was 98.70%. The above results show that the heating operation does not cause significant decomposition of etomomod. Based on the above, it is inferred that Form D is an anhydrous substance.

[0084] Analysis results:

[0085] Purity: 98.70%.

[0086] 1 H-NMR (400MHz, DMSO-d6): δ = 8.54 (s, 1H), 8.05-7.80 (m, 5H), 7.75-7.69 (m, 2H), 7.68-7.63 (m, 2H), 7.32 (d, J = 8.2Hz, 2H), 5.4 2(t,J=5.0Hz,2H),3.56(d,J=4.3Hz,4H),2.83(q,J=7.6Hz,2H),2.71-2.63(m,2H),1.90-1.80(m,2H),1.30(t,J=7.6Hz,3H).

[0087] Example 6 Solid-state stability of Etomod Form A and Form B

[0088] Through polymorph screening of Etomod, a total of 4 crystal forms were found, named as Crystal Form A, Crystal Form B, Crystal Form C, and Crystal Form D. Among them, Crystal Form C is a hydrate crystal form but is unstable. It is easy to lose water and transform into Crystal Form A during drying and storage, and it is difficult to obtain a pure phase; Crystal Form D is an anhydrous crystal form obtained by heating experiments, which is difficult to enlarge. In summary, further evaluation is conducted on Crystal Form A and Crystal Form B of Etomod.

[0089] Samples of Etomod Form A and Form B were placed under 60°C, 92.5% RH, light and 45°C / 75% RH conditions, respectively. The samples were taken before and after placement and the crystal form was determined by XRPD. The results are shown in Table 3. The XRPD comparison spectra of Etomod Form A and Form B after stability placement are shown in Table 3. Fig.17 and Fig.18 The results show that Form A is stable for at least 30 days at 60°C, 92.5% RH, light and 45°C / 75% RH, and Form B is stable for at least 30 days at 60°C and light. However, Form B transforms into Form C after being placed at 92.5% RH and 45°C / 75% RH for 5 days.

[0090] The main purity of Form A did not change significantly after being placed at 40°C / 75%RH, 60°C and 92.5%RH for 30 days, and the main purity decreased slightly after being placed under light conditions for 30 days; the main purity of Form B did not change significantly after being placed at 40°C / 75%RH, 60°C and 92.5%RH for 30 days, and the main purity decreased to a certain extent after being placed under light conditions for 30 days.

[0091] Table 3 Comparison of solid state stability of Form A and Form B

[0092]

[0093] Example 7 Dynamic Solubility Study of Etomod Form A and Form B

[0094] Samples of Atommod crystal form A and crystal form B were taken and prepared into saturated solutions at 37°C in FaSSIF (Fasted State Simulated Intestinal Fluid, artificial simulation of fasting intestinal fluid, pH 8.0), FeSSIF (Fed State Simulated Intestinal Fluid, artificial simulation of intestinal fluid after eating, pH 5.0), SGF (Simulated Gastric Fluid, artificial simulation of gastric fluid, pH 1.0), pH = 1.0 hydrochloric acid aqueous solution, pH = 4.0 acetic acid-sodium acetate buffer system, pH = 6.8 phosphate buffer system and water. The solutions were filtered after 1 hour / 2 hours / 4 hours / 24 hours, and the actual concentration of the sample in the solution was determined by high performance liquid chromatography (HPLC) (the filtrate was diluted as needed), and the crystal form of the solid before and after the experiment was characterized by XRPD to check whether a phase change occurred. The experimental results are shown in Table 4.

[0095] Table 4 Comparison of solubility of Form A and Form B

[0096]

[0097]

[0098] The results showed that the solubility of Form A in FaSSIF, FeSSIF, pH = 1.0 hydrochloric acid aqueous solution, pH = 6.8 phosphate buffer system and water was slightly higher than that of Form B, and Form B had undergone crystal transformation in the solvent. This result shows that Form A is an advantageous form suitable for drug development.

[0099] Example 8 Investigation of the equilibrium solubility of crystalline form A and crystalline form B of etomomod

[0100] Atommod crystal form A and crystal form B were prepared into solutions with ethanol, acetone and ethyl acetate at room temperature, respectively. After 24 hours of equilibrium, the saturated solutions were filtered respectively, and the content of the sample in the saturated solution was determined by high performance liquid chromatography (HPLC) (the filtrate was diluted as needed), and the crystal form of the solid before and after the experiment was characterized by XRPD to check whether a phase change occurred. The experimental results are shown in Table 5. The results show that the solubility of crystal form A in acetone and ethyl acetate at room temperature is slightly higher than that of crystal form B, and crystal form B has undergone crystal transformation in the medium.

[0101] Table 5

[0102]

[0103]

[0104] Example 9 Morphological Study of Atommod Form A and Form B

[0105] The microscopic morphology of the samples of iomod crystal form A and crystal form B was studied. The morphology and particle size of crystal form A and crystal form B were observed under an optical microscope at a magnification of 40. The results of the microscopic observation are shown in Fig.25 and Fig.26 The crystal form A is irregularly flake-shaped, with a raw material particle size of less than 35 μm and a long / short diameter ratio of 1 to 2; the crystal form B is agglomerated and spherical, with a raw material particle size of less than 20 μm.

[0106] Example 10 Mechanical stability of etomode crystalline form A and crystalline form B

[0107] Weigh 50 mg of crystalline form A and crystalline form B of Etomod, grind them clockwise for 5 minutes using an agate mortar, and perform XRPD tests on the samples before and after grinding. The results are shown in Fig.19 and Fig. 20 The XRPD results showed that the crystal form of Form A remained unchanged after grinding, while Form B partially transformed into Form C after grinding. The mechanical stability of Form A was better than that of Form B.

[0108] Example 11 Hygroscopicity of Etomod Form A and Form B

[0109] The samples of Etomod crystal form A and crystal form B were taken for dynamic moisture adsorption test. The results are as follows: Figure 5 and Fig.10 As shown in the figure, the test results show that Form A has no or almost no hygroscopicity (at 24.3°C, 90% RH water absorption increases weight by 0.14%), while Form B has hygroscopicity (at 25.0°C, 90% RH water absorption increases weight by 4.6%). After the dynamic moisture adsorption test, Form A did not undergo crystal transformation, while Form B transformed into Form C. The XRPD comparison results show Fig.23 and Fig.24 middle.

[0110] Example 12 Fluidity of Etomod Form A and Form B

[0111] The powder properties of the API will affect its flowability. The angle of repose and Hausner ratio tests were performed on the crystalline form A and crystalline form B of Etomod to compare their flowability. The results of the flowability evaluation are shown in Table 7, and the flowability of crystalline form A and crystalline form B is comparable.

[0112] Repose angle test method:

[0113] This experiment uses the injection method and the residual cone method to determine the repose angle of two crystalline APIs and analyze their fluidity. The specific operation is: inject the powder into the center of a disk of a limited diameter until the material on the bevel of the powder accumulation layer automatically flows out along the edge of the disk, stop injecting, measure the cone height (H), and calculate the repose angle in combination with the disk diameter (D = 2r), tanQ = H / r. The repose angle test results are shown in Table 6. Test method for bulk density and tap density:

[0114] This experiment uses a vibrator and is measured according to the fixed volume method. The specific operation is as follows: put the weighed powder into a 50-mL measuring cylinder and fix the measuring cylinder on a support. Set the vibration to 55±5 times per minute for 6-8 minutes. Measure the volume change of the powder in the measuring cup. The ratio of the powder mass to the volume of the material before vibration (50mL) is the bulk density of the powder, and the ratio of the powder mass to the volume of the material after vibration is the tap density of the powder.

[0115] The method for converting the Hausner ratio and compression is as follows. The description of the Hausner ratio and fluidity is shown in Table 8:

[0116] Material Hausner ratio = tap density / bulk density

[0117] Material compression degree = (tapped density - bulk density) / tapped density

[0118] Table 6 Physical properties of Form A and Form B

[0119]

[0120] Table 7 Fluidity of Form A and Form B

[0121]

[0122] Table 8 Relationship between Hausner ratio and liquidity

[0123] Hausner Liquidity Description 1.00-1.11 Very good liquidity 1.12-1.18 Good liquidity 1.19-1.25 Good or medium fluidity 1.26-1.34 Liquidity is OK 1.35-1.45 Poor liquidity 1.46-1.59 Very poor liquidity

[0124] Example 13 Adhesion of Etomod Form A and Form B

[0125] Take the crystalline form A and the crystalline form B of Etomod and put them into a ziplock bag of fixed size, seal the seal, flip it at a speed of 5 rpm for 10 minutes, then change the direction and continue flipping at a fixed speed for 10 minutes, pour out the raw materials in the bag, accurately weigh the remaining raw material mass, and calculate the adsorption rate.

[0126] The adsorption rate is calculated as follows:

[0127] Adsorption rate = (initial material mass - remaining material mass) / contact surface area

[0128] The adhesion results of crystalline form A and crystalline form B of etomomod are shown in Table 9. From the results, it can be seen that the adsorption rates of crystalline form A and crystalline form B are comparable.

[0129] Table 9

[0130]

[0131] Example 14 Compressibility of Etomod Form A and Form B

[0132] Etomod crystal form A and crystal form B were used for tableting evaluation. In this experiment, a 6 mm diameter die was used to compress the samples under the same pressure. After the tablets recovered elastically, the radial crushing force F, diameter D, and thickness L of the tablets were measured, and the tensile strength of the tablets was calculated by the following formula, where tensile strength Ts = 2F / ΠDL.

[0133] The compressibility evaluation results of Etomod Form A and Form B are shown in Table 10, and the XRPD results before and after compression are shown in Fig.21 and Fig. 22 The results show that the viscosity of Form A is lower than that of Form B, indicating that it is more suitable for preparing solid preparations.

[0134] Table 10

[0135]

[0136] The applicant declares that the present invention illustrates the crystal form of etomomod and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A crystalline form A of etomomod, characterized in that: The crystal form A has the following diffraction peaks at 2θ diffraction angles on the X-ray diffraction pattern: 9.295°±0.2°, 14.026°±0.2°, 17.107°±0.2°, 17.774°±0.2°, 21.458°±0.2°, 21.937°±0.2°, 22.396°±0.2°, 26.883°±0.2°, 28.236°±0.2°, 28.534°±0.2°; The method for preparing the crystal form A of Etomod comprises the following steps: adding an Etomod sample to methanol, heating to dissolve, and evaporating the solvent to obtain the crystal form A; The temperature is raised to 50-60°C.

2. The method for preparing the crystalline form A of Etomod according to claim 1, characterized in that: The preparation method comprises the following steps: adding an etomomod sample into methanol, heating to dissolve, and evaporating the solvent to obtain crystal form A.

3. The preparation method according to claim 2, characterized in that: The temperature is raised to 50-60°C.

4. A pharmaceutical composition, characterized in that The pharmaceutical composition comprises the crystalline form A of etomomod as described in claim 1, and pharmaceutically acceptable excipients.

5. Use of the crystalline form A of etomomod according to claim 1 in the preparation of an S1P1 receptor immunosuppressant.